2004
DOI: 10.2519/jospt.2004.34.5.235
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Function of the Upper and Lower Parts of the Serratus Anterior Muscle Using Surface Electromyography

Abstract: Study Design: Prospective single-group repeated-measures design. Objective: To use electromyographic (EMG) analysis during muscle testing to determine if there is a difference in function of the upper and lower parts of the serratus anterior (SA) muscle. Background: The SA muscle is a very important scapular protractor and upward rotator. Authors have anatomically described the muscle as being divided into 2 or 3 parts, and have suggested that the upper part is more suited for protraction and the lower part fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 21 publications
0
56
0
1
Order By: Relevance
“…The other two electrodes were applied to both SAs parallel to the muscle fibers midway between the pectoralis major and latissimus dorsi below the axilla area. The reference electrode was applied to the left ankle on the medial malleolus 6,13,15,20,[26][27][28]32) . To perform maximal voluntary contractions (MVC) of a subject's UT (MVC UT ), the subject sat without a back support, and the neck side-bent to the same side, rotated to the opposite side and extended as resistance is applied at the occipital and shoulder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other two electrodes were applied to both SAs parallel to the muscle fibers midway between the pectoralis major and latissimus dorsi below the axilla area. The reference electrode was applied to the left ankle on the medial malleolus 6,13,15,20,[26][27][28]32) . To perform maximal voluntary contractions (MVC) of a subject's UT (MVC UT ), the subject sat without a back support, and the neck side-bent to the same side, rotated to the opposite side and extended as resistance is applied at the occipital and shoulder.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, sufficiently strong scapular muscles can maintain an adequate scapular position in the shoulder girdle 12) . In addition, a force couple made up of the SA and UT rotates the scapula upwardly and affects the function of the upper extremity 6, 9, 13, 18, 24−28) , and this has been widely discussed in terms of coordination and the importance of the force couple and scapular muscle strengthening 9,13,26,27,29) . It has previously been reported that insufficient strength of the scapular muscles led to scapular deviations in the shoulder girdle when performing open kinetic chain exercises.…”
Section: Division Of Physical Therapy Education School Of Allied Heamentioning
confidence: 99%
“…2,4,15 As the humerus is elevated, the serratus anterior assists in upwardly rotating and posteriorly tipping the scapula and prevents scapular winging by keeping the scapula flat on the thorax. 2,4,15 Impaired serratus anterior activation has been associated with altered scapular kinematics and has been suggested as one mechanism underlying shoulder impingement syndromes. 9,12 Impaired serratus anterior activation may also lead to compensatory overactivation of synergists, namely the trapezius.…”
mentioning
confidence: 99%
“…For each position, the transducer was placed at the level of the inferior angle of the scapula, corresponding to the lower portion of the SA. It has been hypothesized that the primary action of the lower portion of SA is upward rotation while the upper portion of the SA primarily protracts the scapula [29]. Because the transducer was placed on the inferior portion of the SA muscle and the push up plus results in scapular protraction, the change in thickness recorded at the lower portion of the SA for the push-up plus may not have been accurate.…”
Section: Discussionmentioning
confidence: 99%